Sulforaphane Attenuates Chronic Intermittent Hypoxia-Induced Brain Damage in Mice via Augmenting Nrf2 Nuclear Translocation and Autophagy - Li, Xiucui; Ying, Huiya; Zhang, Zilong; Yang, Zijing; You, Cancan; Cai, Xiaohong; Lin, Zhongdong; Xiao, Yanfeng (Frontiers in Cellular Neuroscience, 2022)
Obstructive sleep apnea hypopnea syndrome (OSAHS), typically characterized by chronic intermittent hypoxia (CIH), is associated with neurocognitive dysfunction in children. Sulforaphane (SFN), an activator of nuclear factor E2-related factor 2 (Nrf2), has been demonstrated to protect against oxidative stress in various diseases. However, the effect of SFN on OSAHS remains elusive. In the present research, we investigated the neuroprotective role of SFN in CIH-induced cognitive dysfunction and underlying mechanisms of regulation of Nrf2 signaling pathway and autophagy. Chronic intermittent hypoxia (CIH) exposures for 4 weeks in mice, modeling OSAHS, contributed to neurocognitive dysfunction, manifested as increased working memory errors (WME), reference memory errors(RME) and total memory errors (TE) in the 8-Arm radial maze test. SFN treatment ameliorated neurocognitive dysfunction in CIH mice, demonstrating less RME, WME and TE. Also, SFN effectively alleviated apoptosis of hippocampal neurons following CIH by decreased TUNEL positive cells, down-regulated cleaved-caspase3, and up-regulated Bcl-2. SFN protects hippocampal tissue from CIH-induced oxidative stress as evidenced by elevated superoxide dismutase (SOD) activities and reduced methane dicarboxylic aldehyde (MDA). In addition, we found that SFN promoted autophagy activation and Nrf2 nuclear translocation to hold an antioxidative function on CIH-induced neuronal apoptosis in hippocampus. Overall, our findings indicated that SFN reduced the apoptosis of hippocampal neurons through antioxidant effect of Nrf2 and autophagy in CIH-induced brain damage, which highlights the potential of SFN as a novel therapy for OSAHS-related neurocognitive dysfunction.